2009
DOI: 10.1155/2009/103784
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Associated Monoclonal Gammopathy That Resolved after Successful Liver Transplant

Abstract: Monoclonal gammopathy of undetermined significance (MGUS) has been most commonly associated with diseases like multiple myeloma, Waldenstrom's macroglobulinemia, primary systemic amyloidosis, HIV, and other lymphoproliferative disorders. There has been an isolated report of MGUS in patients coinfected with HIV and Hepatitis B, as the work by Amara et al. in 2006. Here, we report a case of IgA-kappa light chain gammopathy secondary to Hepatitis B infection, which resolved after liver transplantation. To our kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“… 25 Recently, a retrospective study showed that patients with non-hepatitis-associated cryoglobulinemic glomerulonephritis were associated with hematologic conditions and responded well to clone-directed therapy. 5 There has been no evidence whether the use of clone-directed therapy in patients with monoclonal gammopathy-related mixed cryoglobulinemia but without hematologic malignancy (such as patients with chronic HBV or HCV infection) 26 28 could result in better disease control and prevent malignancy transformation.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Recently, a retrospective study showed that patients with non-hepatitis-associated cryoglobulinemic glomerulonephritis were associated with hematologic conditions and responded well to clone-directed therapy. 5 There has been no evidence whether the use of clone-directed therapy in patients with monoclonal gammopathy-related mixed cryoglobulinemia but without hematologic malignancy (such as patients with chronic HBV or HCV infection) 26 28 could result in better disease control and prevent malignancy transformation.…”
Section: Discussionmentioning
confidence: 99%